Erinnerungskultur und kultureller Widerstand in den palästinensischen Gebieten: Jenin, »Cinema Jenin« und das »Freedom Theatre« - Rohrbach, Anne (transcript, 2017)
Projects of cultural resistance reveal dynamics of political contra-diction in a fragmented society. In the face of the current political situation, projects geared towards dialog are pressing.